(untitled) (International Journal of Engineering and Computer Science, 2021)
Interest in Robotics and Artificial Intelligence is growing today and impacting many industries. Robotics and Artificial Intelligence have received attention and already produced the most significant results in complicated fields of services, such as consulting, law, and financial services. Today, banks, asset management companies, and insurance companies are challenged to renew their business activities more radically than ever before as the digital revolution is shaping the business environment in these sectors. Changes in the ways of delivering financial services are firm examples of this fast-paced digital revolution. The term FinTech has emerged during the past years to summarise this new technological development in finance. New approaches to finance are reviewed today with crowdfunding and peer-to-peer lending being familiar examples of FinTech. Technologies of big data, machine learning, and blockchain are also included within FinTech. There are concerns on how these new solutions are going to impact the traditional financial sector. The impact of Artificial Intelligence is discussed regarding the digitalisation of property finance. Credit decisions, risk management, fraud prevention, trading, and personalised banking are examples of processes of specific financial services where Artificial Intelligence is applied today. Personalised banking is possibly the most profound revolution in modern wealth management advisory services. Digital investment advice is an innovation in the field of FinTech. For extensive masses of private and retail investors, automated advisory services in wealth management enormously widen the accessibility of investment advisory services that previously have required exclusive banks or wealthy familial backgrounds to afford. The advantage of these facilities is lower fees, however, costs as regards the personalised pricing of investment products might be higher.